Temperature Induced Physiological Reaction Norms of the Coccolithophore Gephyrocapsa oceanica and Resulting Coccolith Sr/Ca and Mg/Ca Ratios - Müller, Marius N.; Blanco-Ameijeiras, Sonia; Stoll, Heather M.; Mendez-Vicente, Ana; Lebrato, Mario (Frontiers in Earth Science, 2021)
Coccolithophores are one of the major contributors to the pelagic production of calcium carbonate and their fossilized remains are a key component of the biogeochemical cycles of calcium (Ca), magnesium (Mg) and other divalent cations present in the intracellular precipitated calcitic structures (coccoliths). The geochemical signature of coccoliths (e.g. Sr/Ca and Mg/Ca ratios) is used as paleoproxy to reconstruct past environmental conditions and to understand the underlying physiological precipitation kinetics. Here, we present the elemental fractionation of Sr and Mg in calcite of the coccolithophore Gephyrocapsa oceanica from controlled laboratory experiments applying an extended temperature gradient (12 to 27 °C). The physiological reaction norm of G. oceanica, in terms of growth rate, exhibited optimum behaviour while the partition coefficient of Sr (DSr) was linearly correlated with temperature and DMg indicated no specific trend. Our results indicate: (1) a presumably secondary physiological control of DSr, and (2) the importance of calibrating coccolithophore-based proxies using experiments that include the full physiological reaction norms (i.e. a possible non-linear response) to environmental drivers (e.g. temperature, salinity, pH, etc.). The presented results contribute to an improved understanding of the underlying physiological kinetics involved in regulating coccolith elemental fractionation and give additional implications for designing future laboratory experiments to calibrate and apply coccolithophore based paleoproxies on the fossil sediment record.